2017
DOI: 10.3390/molecules22010144
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Solid-State Transformations of Coordination Bonds: From the Ball Mill to the Aging Chamber

Abstract: Controlling the formation of coordination bonds is pivotal to the development of a plethora of functional metal-organic materials, ranging from coordination polymers, metal-organic frameworks (MOFs) to metallodrugs. The interest in and commercialization of such materials has created a need for more efficient, environmentally-friendly routes for making coordination bonds. Solid-state coordination chemistry is a versatile greener alternative to conventional synthesis, offering quantitative yields, enhanced stoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(105 citation statements)
references
References 251 publications
(322 reference statements)
1
104
0
Order By: Relevance
“…[31][32][33] Mechanochemistry,t hat is, reactions induced or sustained by mechanicalm illing or shear,h as recently emerged as aw ay to conductc hemical transformationsi ne ither the complete absence of solvents or,i nt he case of liquid-assistedg rinding (LAG), [34][35][36] in the presence of as mall amount of al iquid that can enhancea nd direct reactivity while avoiding solubility limitations. It was recently shown that enzymes can retain activity under mechanochemicalconditions, [37][38][39][40][41][42] and our group has reported that efficient mechanoenzymatic hydrolysis of cellulose can be achieved by repeating cycles of millinga nd aging (static incubation) [43][44][45] of physical mixtures of the solid substrate, lyophilized cellulase enzymes,a nd as mall amount of water.T his process, termed reactive aging (RAging), led to significantly higher glucosec oncentrationst han previously reported methods and, importantly,w ithoutt he need for biomass pretreatment or the use of harsh chemicals. [46] Because the amount of water in RAging is orders of magnitude lower than in conventional solution processes and stoichiometrically comparable to that of the substrate, we speculated that RAging should provide am ore suitable environmentf or chitinase activity compared with conventionalb iocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Mechanochemistry,t hat is, reactions induced or sustained by mechanicalm illing or shear,h as recently emerged as aw ay to conductc hemical transformationsi ne ither the complete absence of solvents or,i nt he case of liquid-assistedg rinding (LAG), [34][35][36] in the presence of as mall amount of al iquid that can enhancea nd direct reactivity while avoiding solubility limitations. It was recently shown that enzymes can retain activity under mechanochemicalconditions, [37][38][39][40][41][42] and our group has reported that efficient mechanoenzymatic hydrolysis of cellulose can be achieved by repeating cycles of millinga nd aging (static incubation) [43][44][45] of physical mixtures of the solid substrate, lyophilized cellulase enzymes,a nd as mall amount of water.T his process, termed reactive aging (RAging), led to significantly higher glucosec oncentrationst han previously reported methods and, importantly,w ithoutt he need for biomass pretreatment or the use of harsh chemicals. [46] Because the amount of water in RAging is orders of magnitude lower than in conventional solution processes and stoichiometrically comparable to that of the substrate, we speculated that RAging should provide am ore suitable environmentf or chitinase activity compared with conventionalb iocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…The second issue can be addressed by the concept of mechanochemistry. Mechanochemistry has been applied repeatedly as a sustainable and cost‐effective alternative to conventional synthesis concepts in the fields of pharmaceutical, organic, and inorganic chemistry, especially in the field of metal–organic frameworks (MOFs) . Mechanochemical syntheses rely on the input of mechanical energy to initiate chemical reactions, for instance by grinding solids in high‐energy ball mills.…”
Section: Introductionmentioning
confidence: 99%
“…The second issue can be addressed by the concept of mechanochemistry.M echanochemistryh as been appliedr epeatedly as as ustainable and cost-effective alternative to conventional synthesis concepts in the fields of pharmaceutical, [43,44] organic, [45][46][47] and inorganic chemistry,e specially in the field of metal-organic frameworks (MOFs). [48][49][50][51][52] Mechanochemicals yntheses rely on the input of mechanicale nergy to initiate chemical reactions, for instanceb yg rinding solids in high-energy ball mills. In contrastt om any conventionals yntheses, mechanochemical pathwaysa llow the production of materials without the use of any solvent, [53,54] with high yields, [55,56] short reaction times, [12,57] and easy scalability.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanochemical reactions are of great interest because of their synthetic advantages such as scalable production, zero reaction waste, reduced reaction times, enhanced selectivity and different reactivities compared with reactions performed in solution . Recently, mechanochemical syntheses of MOFs have been demonstrated via mortar grinding, ball milling, microwave, and twin‐screw extrusion . Although there are reports of MOFs being synthesized by mechanochemical reactions, the preparation of morphology controlled hierarchical MOFs superstructures is still challenge.…”
Section: Introductionmentioning
confidence: 99%